2005
DOI: 10.1086/508946
|View full text |Cite
|
Sign up to set email alerts
|

To Quantize or Not to Quantize: Fact and Folklore in Quantum Gravity

Abstract: Does the need to find a quantum theory of gravity imply that the gravitational field must be quantized? Physicists working in quantum gravity routinely assume an affirmative answer, often without being aware of the metaphysical commitments that tend to underlie this assumption. The ambition of this article is to probe these commitments and to analyze some recently adduced arguments pertinent to the issue of quantization. While there exist good reasons to quantize gravity, as this analysis will show, alternativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 14 publications
0
42
0
3
Order By: Relevance
“…Interesting new work by Terno (2004) and Peres andTerno (1996,2001) on the generic feature worry-in this case a worry about the correspondence principle-is discussed in Wüthrich (2005). Wüthrich, correctly in my view, sides with Callender and Huggett, and Mattingly in rejecting the claim that gravity must be quantum mechanical in any quantum gravity (again broadly construed).…”
Section: Objections To Mongrel Gravity In Generalmentioning
confidence: 97%
See 1 more Smart Citation
“…Interesting new work by Terno (2004) and Peres andTerno (1996,2001) on the generic feature worry-in this case a worry about the correspondence principle-is discussed in Wüthrich (2005). Wüthrich, correctly in my view, sides with Callender and Huggett, and Mattingly in rejecting the claim that gravity must be quantum mechanical in any quantum gravity (again broadly construed).…”
Section: Objections To Mongrel Gravity In Generalmentioning
confidence: 97%
“…While still generally accepted in much of the physics community and the philosophy of physics community, arguments indicating the impossibility of any mongrel theory of gravity are being treated with ever greater critical scrutiny (Callender and Huggett 2001, Mattingly 1999], 2006, Wüthrich 2005. As a result some of the standard arguments have been laid to rest.…”
Section: Objections To Mongrel Gravity In Generalmentioning
confidence: 99%
“…Johnson and Walker (2005) reported that Sir Michael asserted that "…understanding space is the fundamental problem of physics, and his talk focused extensively on the relationship between mathematics and physics, particularly with regard to the nature of space.". Over the years many researchers have been preoccupied with the true nature of the emptiness that is space and its connection to the problem of gravity, among them Sakharov (1967), Zel'dovich (1967), Misner, Thorn and Wheeler (1971), Puthoff (2001), and Wüthrich (2005) to name a few.…”
Section: Introductionmentioning
confidence: 99%
“…In Wuthrich's () interpretation of Snyder's () and Doplicher's () arguments, the operational definition of these distances is not possible because the created black hole prevents signals from escaping and completing the measurement. However, even if the measurement could ( per impossibile ) be completed, the problem would remain, because spacetime would have been destroyed, and it would not be clear what the signal is supposed to be a measurement of.…”
mentioning
confidence: 99%
“…Semi‐classical gravity would be an exception, as it claims that (a slightly modified version of) GR is true at all scales without having to be quantized. This approach however is not without its problems (Wüthrich, ).…”
mentioning
confidence: 99%